2017
DOI: 10.2131/jts.42.763
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage differentiation induced by PMA is mediated by activation of RhoA/ROCK signaling

Abstract: -In order to investigate the effects of RhoA/ROCK signaling in macrophage differentiation, we used 100 ng/mL PMA to induce macrophage differentiation from U937 cells in vitro. The observation of cell morphology and the expression of CD68 and SR-A were performed to confirm the differentiation induced by PMA. Western blot analysis showed that the expression of ROCK1 and ROCK2 and the phosphorylation of MYPT1 were significantly increased after PMA treatment. Pulldown assay showed that the activation of RhoA was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 30 publications
3
34
0
1
Order By: Relevance
“…Also, we found that asthmatic lung tissues showed activated RhoA signaling, and inhibition of RhoA signaling prevented CRE-induced airway inflammation and remodeling in a chronic mouse model of asthma (30). Furthermore, the activation of RhoA signaling has been associated with macrophage polarization (62,63). In this study, we provided evidence that Ccl2 can activate RhoA signaling, and that inhibition of RhoA signaling can block Ccl2-induced M1 macrophage polarization.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Also, we found that asthmatic lung tissues showed activated RhoA signaling, and inhibition of RhoA signaling prevented CRE-induced airway inflammation and remodeling in a chronic mouse model of asthma (30). Furthermore, the activation of RhoA signaling has been associated with macrophage polarization (62,63). In this study, we provided evidence that Ccl2 can activate RhoA signaling, and that inhibition of RhoA signaling can block Ccl2-induced M1 macrophage polarization.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, the insufficient amount of Ccl2 caused by miR-511-3p fails to polarize macrophages into an inflammatory M1 phenotype, thereby leading to the reduction of allergic inflammation. ferentiation induced by PMA (19,39). Furthermore, we have previously demonstrated that Ptgds (encoding hematopoietic prostaglandin D synthase), which catalyzes the conversion of PGH2 to PGD2, may be one of the direct target genes for miR-511-3p (10).…”
Section: Discussionmentioning
confidence: 99%
“…This is of vital importance as cellular signaling is largely governed by the regulation of expression of kinases and phosphatases in a cell type-specific manner or upon cell activation (51-53). One of the major findings of this study is the differential expression of key regulatory kinases implicated in cell cycle regulation including cyclin-dependent kinases, NEK family of serine-threonine kinases as well as cAMP/PKA-induced signaling that are collectively responsible for enrichment of signaling pathways involved in differentiation, maturation, and regulation of actin cytoskeleton dynamics (54, 55). Interestingly, a pronounced decrease in the expression of vital regulatory kinases in cell cycle entry and checkpoint including the cyclin-dependent kinases has been reported in a previous study exploring the role of kinases in monocyte-macrophage differentiation (22).…”
Section: Discussionmentioning
confidence: 99%
“…RhoGTP enzyme family members, including Rho, Rac and Cdc42, are closely associated with cytoskeleton reorganization and serve an important role in cell motility, migration and invasion (34). The degree of Rac signaling plays a crucial role in the balance between differentiation and proliferation; cellular Rac1 is indispensable for differentiation (35), and RhoA/ROCK signaling plays an important role in differentiation induction (36). The activation of Rho and Rac1 can phosphorylate the kinase ROCK and activate LIMK1, as Rac can activate LIMK1, which induces cofilin 1 phosphorylation at Ser3 and thus regulates the actin cytoskeleton; this process indicates the formation of the Rac1-ROCK1/LIMK1-cofilin signaling pathway by regulating tumor cell migration and invasion (37,38).…”
Section: Groupmentioning
confidence: 99%